2015
DOI: 10.1074/jbc.m114.600932
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Significant Amino Acids in Multiple Transmembrane Domains of Human Transient Receptor Potential Ankyrin 1 (TRPA1) for Activation by Eudesmol, an Oxygenized Sesquiterpene in Hop Essential Oil

Abstract: Background: Transient receptor potential ankyrin 1 (TRPA1) is activated by many spicy compounds by unknown mechanisms. Results: The amino acids critical for the activation of TRPA1 by the hop-derived sesquiterpene ␤-eudesmol were identified. Conclusion: Multiple transmembrane domains are crucial for ␤-eudesmol-derived TRPA1 activation. Significance: New insight for activation mechanism of TRPA1 is revealed by our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…It should be noted that ferutinin, a sesquiterpenic compound isolated from Ferula spp., has Ca 2+ ionophore properties [54] and can also induce Ca 2+ -dependent mitochondrial depolarization [55]. Another sesquiterpene, eudesmol, was recently reported as an activator of TRPA1 channels [56]. Thus, because the tested essential oils, with the exception of FEO Fr , contain eudesmane-type sesquiterpenes, we also cannot exclude roles of these sesquiterpenes in modulation of Ca 2+ flux in phagocytes by those essential oil extracts.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted that ferutinin, a sesquiterpenic compound isolated from Ferula spp., has Ca 2+ ionophore properties [54] and can also induce Ca 2+ -dependent mitochondrial depolarization [55]. Another sesquiterpene, eudesmol, was recently reported as an activator of TRPA1 channels [56]. Thus, because the tested essential oils, with the exception of FEO Fr , contain eudesmane-type sesquiterpenes, we also cannot exclude roles of these sesquiterpenes in modulation of Ca 2+ flux in phagocytes by those essential oil extracts.…”
Section: Discussionmentioning
confidence: 97%
“…The ARs form short helices assembled into an asymmetrical cylindrical tertiary structure possessing a surface available for protein interactions [22]. The influence of alterations within the individual ARs is relatively unexplored [23,24] compared with studies examining the transmembrane bundle [25][26][27][28][29] or C-terminal domain [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Electrophilic compounds are known to activate TRPA1 through covalent modification of cysteines and a lysine in the N-terminal region (12,13). In addition, the S5/S6 domain may serve as a target region for nonelectrophilic agonists, including menthol (14), eudesmol (15), and protons (16), or several antagonists (17,18), including the potent inhibitor A-967079 (14,(19)(20)(21). Furthermore, a recent electron cryo-microscopy (cryo-EM) study (22) has revealed the high-resolution structure of TRPA1 bound to an agonist or antagonists.…”
mentioning
confidence: 99%